Association of STAT6 genetic variants with childhood atopic dermatitis in Taiwanese population. Issue 3 (September 2015) - Lee, Yungling Leo; Yen, Jeffrey Jong-Young; Hsu, Li-Chung; Kuo, Nai-Wei; Su, Ming-Wei; Yang, Ming-Fong; Hsiao, Yu-Ping; Wang, I-Jen; Liu, Fu-Tong
Highlights: We used HapMap Project data and TCHS cohort to compensate for the limitation of candidate-gene approach. We performed deep sequencing to identify novel variants around rs324011 in STAT6 gene and a total of seven variants were found, including rs167769. T allele of rs324011 increased the risk of childhood AD and haplotypes (rs167769/rs324011) was significantly associated with childhood AD in Taiwanese population. T alleles of both rs324011 and rs167769 would enhance STAT6 promoter activities in luciferase assay. Abstract: Background: Atopic dermatitis (AD) is the single most common allergic disease in children. STAT6 has been noted as a hub molecule in IL-4 mediated response and AD pathogenesis. However, the association between STAT6 genetic variants and childhood AD has never been thoroughly examined. Objective: We investigate the association between STAT6 genetic variants and childhood AD risk in Taiwanese population. Methods: We used data from the Han Chinese in Beijing genome panel of International HapMap Project and the Taiwan Children Health Study cohort to investigate the association of STAT6 genetic variants and childhood AD risks. Four tagged SNPs were selected from HapMap database and rs324011 was most significantly associated with childhood AD. Subsequently, deep sequencing around rs324011 and unconditional/conditional logistic models were applied. Results: rs324011 showed statistical significance for the occurrence of childhood AD (OR: 1.23; 95% CI: 1.01–1.51) and rs167769 showed borderline statistical significance (OR: 1.21; 95% CI: 0.99–1.49). Likelihood ratio tests revealed that haplotypes (rs167769/rs324011) were associated with childhood AD (global p = 0.0018). T alleles of two STAT6 intron2 SNPs, rs324011 and rs167769, increased STAT6 promoter activity significantly in luciferase reporter assay. Conclusion: T allele of rs324011 in STAT6 would increase the risk of AD occurrence in children. Haplotypes of rs324011/rs167769 were also significantly associated with childhood AD in Taiwanese population.